Synthesis And Characterisation Of Colloidal Alpo-S Nanocrystals Templated By L-Ethyl-2,3- Dimetiiylimidazolium Hydroxide - Ng Tat Lun, Darren (2015)
Colloidal stable nanosized AIPO-S crystals were synthesised via hydrothermal method using a new template, l-ethyl-2,3-dimethylimidazolium hydroxide, [edmim]OH. The syntheses were carried out under various synthesis conditions such as heating time, heating temperature and molar composition of precursor gels to investigate the effects of the conditions on the crystallisation of AIPO-S. The new template, [edmim]OH, had produced colloidally stable AIPO-S nanocrystals with the size in the range of SO-800 nm with low agglomeration and defined shape. Additionally, this study also applied a facile and fast synthesis method whereby the precursor gels were heated with microwave radiation rather than the conventional heating in an oven. This synthesis method allowed AIPO-S nanocrystals to be obtained within several minutes compared to the conventional hydrothermal heating which required several hours for complete crystallisation. Interestingly, the nanocrystals obtained via microwave heating were of smaller sizes due to fast nucleation. The AIPO-S nanocrystals obtained in this study exhibited hexagonal frustum feature with low agglomeration.